CROHN'S DISEASE AND GASTROINTESTINAL REPERCUSSIONS: A DETAILED STUDY OF COMORBIDITIES AND CLINICAL IMPLICATIONS - Ramos , Júlia Cristina de Sousa; Rezende, Eduardo Henrique Mendes; Filho, Murilo Dell Eugenio Costa; Silva, Daniel Oliveira; Schimin, ⁠Mayra Algeri; Araújo, Lucas Torres de; Alves , Natana Carol; Pinheiro , Bruno Barbosa; Lemos, Pedro Henrique Kuert (Brazilian Journal of Implantology and Health Sciences, 2024)
Crohn's disease is a chronic inflammatory condition that affects the gastrointestinal tract, characterized by transmural and segmental inflammation that can involve any part of the digestive system, from the mouth to the anus. This pathology presents a wide range of clinical manifestations, including abdominal pain, diarrhea, rectal bleeding, fistulas, strictures and even extraintestinal complications. The complexity of Crohn's disease lies not only in its varied clinical presentation, but also in its comorbidities and clinical implications, which can significantly affect patients' quality of life and require multifaceted therapeutic approaches. Objective: To identify and synthesize the evidence available in the scientific literature over the last 10 years on the comorbidities and clinical implications of Crohn's Disease, in order to provide a comprehensive and updated view of this aspect of gastrointestinal pathology. Methodology: The systematic review was carried out in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The PubMed, Scielo and Web of Science databases were used to identify relevant studies published in the last 10 years. The descriptors used were "Crohn's disease", "gastrointestinal manifestations", "comorbidities", "clinical implications" and "systematic review". The inclusion criteria involved studies that specifically investigated the comorbidities and clinical implications of Crohn's Disease, with results available in English, Spanish or Portuguese. Exclusion criteria included duplicate studies, case reports and studies with small samples or less robust methods. Results: Analysis of the selected studies revealed a wide variety of comorbidities associated with Crohn's disease, including arthritis, dermatitis, uveitis, osteoporosis and liver disorders. Furthermore, the significant clinical implications of Crohn's disease were highlighted, such as increased risk of hospitalizations, need for intestinal surgeries and impact on patients' quality of life. Conclusion: Crohn's disease presents a clinical complexity that goes beyond intestinal manifestations, with a series of comorbidities and clinical implications that require an integrated and multidisciplinary approach in its management. This review highlights the importance of understanding these aspects to improve the care and quality of life of patients with this chronic gastrointestinal condition.